2019
DOI: 10.4067/s0718-48082019000300199
|View full text |Cite
|
Sign up to set email alerts
|

Predictores psicológicos de la re-ganancia del peso en pacientes bariátricos

Abstract: Recibido (25 de marzo de 2019) Aceptado (09 de mayo de 2019) Resumen La cirugía bariátrica permite una pérdida ponderal significativa y acelerada en el corto plazo. La re-ganancia del peso se observa entre el 15 al 30% de los pacientes. Los factores psicológicos explicarían en mayor medida la recuperación del peso en pacientes bariátricos. El objetivo del presente estudio fue evaluar la capacidad predictiva de las variables "locus de control del peso", "perspectiva temporal" y "autoeficacia, para la re-gananci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
(60 reference statements)
0
3
0
1
Order By: Relevance
“…On the other hand, there are cases in which the patient tends to have an external locus of control, attributing the causes of his weight gain to factors unrelated to his behavior. This is supported by studies that show that an internal locus of control predicts a lower percentage of bariatric patients reneging, acting as a protective factor against patients with an external locus of control [ 57 ]. In practice, these patients usually have the belief that they are following the guidelines correctly but that they are not losing weight because the bariatric intervention has not been performed or has not been successful, or they have cognitive distortions related to a negative vision of the world such as bad luck or everything is against you when in fact they are not aware that they are not following the nutritional guidelines correctly.…”
Section: Main Psychological Barriers That Influence Weight Regainmentioning
confidence: 77%
See 1 more Smart Citation
“…On the other hand, there are cases in which the patient tends to have an external locus of control, attributing the causes of his weight gain to factors unrelated to his behavior. This is supported by studies that show that an internal locus of control predicts a lower percentage of bariatric patients reneging, acting as a protective factor against patients with an external locus of control [ 57 ]. In practice, these patients usually have the belief that they are following the guidelines correctly but that they are not losing weight because the bariatric intervention has not been performed or has not been successful, or they have cognitive distortions related to a negative vision of the world such as bad luck or everything is against you when in fact they are not aware that they are not following the nutritional guidelines correctly.…”
Section: Main Psychological Barriers That Influence Weight Regainmentioning
confidence: 77%
“…All this contributes to the fact that after exercising, the patient has negative sensations or even injuries and pain, which can generate aversion to physical activity and therefore discourage performance in the future. This contributes negatively to weight loss and therefore enhances the circle, as can be seen in Figure 3 [ 57 ].…”
Section: Main Psychological Barriers That Influence Weight Regainmentioning
confidence: 99%
“…Mental health, duration since surgery, preoperative BMI, and comorbidities such as T2D, hypertension, and low LDL are major factors involved in WR which mentioned their mechanisms and management approaches in previous sections. As far as psychological factor is concern, 27.1% of the variance of the WR is due to "locus of control, "present fatalist", and "positive past" [81]. In another study, analysis revealed that, initial age, waist circumference, type 2 diabe-tes, and total weight loss at primary months were associated with either 1-year or 3-year weight loss.…”
Section: Other Predictor Factors Of Weight Regain In Bariatric Surger...mentioning
confidence: 97%
“…Además en nuestro país, el número de cirugías bariátricas tanto en el sector privado como en el sector público ha ido aumentando año tras año (Csendes, 2015;Guzmán et al, 2013). No obstante, todas estas intervenciones no han tenido el impacto esperado en relación a frenar la prevalencia de sobrepeso y obesidad, que sigue en aumento (Ugarte, Quiñones y Vicente, 2019).…”
Section: Introductionunclassified